Information Sources used by Livestock Farmers in Iran - H. Shabanali Fami,; Kh. Kalantari,; A. Asadi, (Journal of Agricultural Extension Management, 2025)
There has been growing global concern over the worsening problems of poverty, hunger and malnutrition in the world, particularly in developing countries during the past few decades. Since 1960, the total human population has increased by 75 percent, but in developing countries it has grown by 97 percent, compared to 28 percent in the industrialized world (Sansoucy, 1995a). One of the challenges facing the world over the next decades is preserving its natural resources while at the same time producing sufficient food to satisfy the demands of a growing human population. World population is expected to grow from 5.5 billion now to about eight billion in the year 2020. Specialists at the International Food Pol icy Research Institute (IFPRI) estimate that the current demand of 1.7 billion tons of cereal s and 206 million tons of meat, may rise by the year 2020 to 2.5-2.8 billion tons of cereals and at least 275- 310 million tons of meat (De Haan, et al., 1997). In spite of the huge progress achieved worldwide in food crop production, almost 800 million people in the developing world do not have enough to eat. If all the worlds ' undernourished people were gathered together, the population of the continent of the hungry would dwarf that of every other continent except Asia (Sansoucy, 1995b, FAO, 1999)